Metathesis of aspiration as the source of anticipatory voicelessness in Basque. Issue 2 (July 2019) - Egurtzegi, Ander
ABSTRACT: In Basque, there is evidence, especially in early loans from Latin, that a sequence #DV(R)T… where D is a voiced stop and T is a voiceless (aspirated) stop was optionally produced with devoicing of the first of these stops. An additional particularity of this sound pattern is that the devoiced word-initial stop typically surfaces with aspiration, while the previously aspirated stop loses it: #DV(R)T (h) … > #T (h) V(R)T… This typologically uncommon sound pattern has been described as assimilation of voicelessness in the literature, or spread of [-voiced]. I propose that this sound pattern is triggered by aspiration, not voicelessness, and that it is a case of metathesis, not assimilation. Under the proposed analysis, aspiration of the second stop in the word is reanalysed as originating in the first stop, an instance of perceptual metathesis . This approach accounts for the distribution of aspirated stops before and after the optional change, and the failure of post-sibilant stops to trigger. This account also has implications for the chronology of aspiration-loss in Western dialects: at the time the earliest Latin loans were borrowed, all Basque dialects still maintained a historical series of aspirated stops. Only later, after this process of optional metathesis, did the Western dialects lose *h and stop aspiration.